2020
DOI: 10.1177/1120672120914491
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of risk–benefit ratio and comparison of post-operative efficacy results between trabeculectomy and canaloplasty

Abstract: Purpose: To estimate a risk–benefit ratio by comparing the efficacy of canaloplasty to trabeculectomy exclusively in pseudophakic eyes with primary open angle glaucoma. Patients and methods: One hundred four eyes that underwent ab externo canaloplasty and 136 eyes that underwent trabeculectomy with mitomycin C 0.02% and collagen matrix implantation were retrospectively compared. The efficacy was evaluated by evaluating the absolute success rate (5 ⩽ intraocular pressure ⩽ 15 mmHg) and the qualified success rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 22 publications
6
14
0
Order By: Relevance
“…Vastardis reported that complete and qualified success rates were 74.31% and 90% with an IOP ≤ 21 mmHg [ 27 ]. Furthermore, Vastardis reported an absolute success rate of 20.19% in advanced POAG [ 28 ]. The reason for the low success rate could be the definition of the success rate (5 ≤ IOP ≤ 15 mmHg), which was lower than usual criteria (IOP ≤ 21 mmHg or IOP ≤ 18 mmHg).…”
Section: Discussionmentioning
confidence: 99%
“…Vastardis reported that complete and qualified success rates were 74.31% and 90% with an IOP ≤ 21 mmHg [ 27 ]. Furthermore, Vastardis reported an absolute success rate of 20.19% in advanced POAG [ 28 ]. The reason for the low success rate could be the definition of the success rate (5 ≤ IOP ≤ 15 mmHg), which was lower than usual criteria (IOP ≤ 21 mmHg or IOP ≤ 18 mmHg).…”
Section: Discussionmentioning
confidence: 99%
“…The results of risk of bias using the ROBINS-1 tool are illustrated in (Supplementary Table S2). Overall, one study had low risk of bias 21 , three studies had serious risk of bias 14,16,28 , and nine studies had moderate risk of bias 12,13,22,[24][25][26][27]29,30 . Bias was more frequently encountered in the "measurement of outcome" domain 12,13,16,[24][25][26]30 .…”
Section: Risk Of Bias Of Included Studiesmentioning
confidence: 99%
“…Overall, one study had low risk of bias 21 , three studies had serious risk of bias 14,16,28 , and nine studies had moderate risk of bias 12,13,22,[24][25][26][27]29,30 . Bias was more frequently encountered in the "measurement of outcome" domain 12,13,16,[24][25][26]30 . In the single randomized controlled trial, it was given an overall high risk of bias, which was driven solely due to high risk of randomization bias [due to no information regarding allocation concealment besides the presence of baseline imbalance between both interventions in terms of affected eye, IOP, and gender] 23 .…”
Section: Risk Of Bias Of Included Studiesmentioning
confidence: 99%
“…Early trabeculectomy filtering procedures were associated with a high rate of complications like hypotony, hypotonic maculopathy, choroidal detachment, suprachoroidal hemorrhage, bleb-related infections, and endophthalmitis [12][13][14][15][16][17][18]. Early cases of bleb leaks, shallow anterior chamber, and hypotony can be resolved with the use of large bandage contact lenses, pressure patching, symblepharon rings, and the Simmons shell.…”
Section: Complications and The Search For Newer Proceduresmentioning
confidence: 99%
“…Early cases of bleb leaks, shallow anterior chamber, and hypotony can be resolved with the use of large bandage contact lenses, pressure patching, symblepharon rings, and the Simmons shell. However, a flat anterior chamber with lens-corneal touch requires immediate surgical intervention to prevent rapid cataract development and irreversible corneal endothelial damage [12][13][14]. Initial studies have reported hypotony and choroidal detachment as late as 2-26 months following primary uncomplicated surgery that warrants a repeat surgery [14,15].…”
Section: Complications and The Search For Newer Proceduresmentioning
confidence: 99%